2021
DOI: 10.3390/su132212557
|View full text |Cite
|
Sign up to set email alerts
|

From Corporate Social Responsibility to Stock Price Crash Risk: Modelling the Mediating Role of Firm Performance in an Emerging Market

Abstract: The literature on the link between corporate social responsibility (CSR) disclosure and stock price crash risk suggests that it is far more complicated than a plain one-to-one relationship. In this study, we examine how CSR disclosure affects the stock price crash risk and whether firm performance acts as a mediating variable in this relationship. The CSR disclosure index is built using the content analysis technique and the GRI criteria. We choose 225 businesses in Vietnam, comprising 159 firms listed on HOSE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…The results show that CSR indirectly affects firms' accounting profitability by enhancing employee commitment and directly affects firms' profitability. CSR disclosure has a negative effect on the share price collapse of listed companies in Vietnam, as confirmed by Thuy et al [66]. Listed companies should perform CSR practices and disclosures to improve enterprise performance and reduce the risk of share price collapse.…”
Section: -5-csr and Ep Under Financing Constraintsmentioning
confidence: 86%
See 1 more Smart Citation
“…The results show that CSR indirectly affects firms' accounting profitability by enhancing employee commitment and directly affects firms' profitability. CSR disclosure has a negative effect on the share price collapse of listed companies in Vietnam, as confirmed by Thuy et al [66]. Listed companies should perform CSR practices and disclosures to improve enterprise performance and reduce the risk of share price collapse.…”
Section: -5-csr and Ep Under Financing Constraintsmentioning
confidence: 86%
“…However, note that research on the relationship between CSR, business financial performance, and democratic leadership style is in its infancy. For example, McGuire et al [66,67] studied the relationship between the level of competence of collegial leaders and CSR and could not confirm any substantive relationship between them. Thomas and Simerly [87], Simerly [88] proved that even when a company's peer leaders are actively focused on social goals, their high salary levels offset the effect of CSR and reduce the company's financial performance.…”
Section: -6-impact Of Leadership On Csr Interactions and Business Fin...mentioning
confidence: 98%
“…Xu et al [ 19 ] found that there was a positive relationship between corporate tax avoidance and the readability of CSR reports. Thuy et al [ 20 ] found that the readability of CSR reports had a negative influence on stock price crash risk. There are many research findings on the readability of CSR reports.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To further verify the mediating effect, we adopted a Sobel test based on Thuy et al's studies [46,47]. The results in Table 6 show that the mediating influence of green innovation behavior on the relationship between green learning orientation and sustainable performance is significant.…”
Section: Mediating Analysismentioning
confidence: 99%